Pengujian faktor risiko umum melalui portofolio excess return - Tanzil, Ivan Chandra; Wijaya, Liliana Inggrit; Marciano, Deddy (Universitas Kristen Maranatha, 2022)
This study aims to examine common risk factors' effects in the Fama and French Five-Factor Model plus Momentum Factor on The Bisnis-27 Index Stocks component during the 2016-2020 period. This research's common risk factors include market risk premium, firm size, book-to-market equity ratio, profitability, investment, and momentum. A quantitative approach will be used in this study by using multiple linear regression. The regression in this study was generated by the common effects model method. This study reveals that a portfolio's excess return is simultaneously affected by common risk factors that are in place this study. The findings in this study show that market risk premium, book-to-market ratio, company size, and momentum positively affect portfolios' excess returns. The greater the market risk premium, the smaller the size of the company, the larger the book-to-market ratio, and the stock's past performance, as reflected by the momentum, has implications for the acquisition of a larger excess return on the portfolio. Meanwhile, there is no significant influence between profitability and investment factor on portfolios' excess returns.